2012
DOI: 10.17265/1934-7359/2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality and Thermal Comfort Evaluation in Latvian Daycare Centers with Carbon Dioxide, Temperature and Humidity as Indicators

Abstract: Latvian children under the age of 7 can spend up to 60 hours per week in daycare centers and therefore it is very important to establish a healthy and comfortable daycare environment that children will find pleasant and stimulating to stay in. This study investigates indoor air quality and thermal comfort within six daycare centers (old, renovated and new-built) in moderate climate zone of Latvia. Measurements of carbon dioxide, air temperature and relative humidity were carried out, and data regarding daycare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Canha [26] obtained high levels of CO 2 (1200 ± 400 ppm) in studies carried out in France. According to research by Stankevic and Lesinskis [27], 75 percent of the educational institutions with natural ventilation (in Latvia) exceeded 1000 ppm carbon dioxide, with a maximum value of 1356 ppm. In other studies [24], the average concentration of CO 2 in 17 educational institutions was analyzed, the median was 1400 ppm, and the maximum concentration was 3613 ppm.…”
Section: Co 2 Concentrationmentioning
confidence: 99%
“…Canha [26] obtained high levels of CO 2 (1200 ± 400 ppm) in studies carried out in France. According to research by Stankevic and Lesinskis [27], 75 percent of the educational institutions with natural ventilation (in Latvia) exceeded 1000 ppm carbon dioxide, with a maximum value of 1356 ppm. In other studies [24], the average concentration of CO 2 in 17 educational institutions was analyzed, the median was 1400 ppm, and the maximum concentration was 3613 ppm.…”
Section: Co 2 Concentrationmentioning
confidence: 99%
“…Studies performed in Latvian education institutions [17], [18] have also shown that the indoor environment is critical in many classrooms. In 2015, the World Health Organization produced a document entitled "School environment: policies and current status" to draw the attention of school administration to indoor air quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Published results from several studies found 75% (out of 6 schools), 89.3% (out of 28 samples) and 90% (out of 91 schools) of measured indoor CO 2 concentrations exceeded 1000 ppm. 9,27,28 Across numerous studies measured indoor CO 2 concentrations ranged from 377 to 2750 ppm. 9,13,15,18,[27][28][29][30][31][32] However, as monitoring methods (e.g.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…9,27,28 Across numerous studies measured indoor CO 2 concentrations ranged from 377 to 2750 ppm. 9,13,15,18,[27][28][29][30][31][32] However, as monitoring methods (e.g. monitoring periods) used in the studies was different, comparing the results is difficult.…”
Section: Environmental Conditionsmentioning
confidence: 99%